Chaminé solar como alternativa para incrementar a ventilação natural em espaços internos - Cavalcanti, Fernando Antonio de Melo Sá (Universidade Federal de São Carlos, 2010)
This work aims to investigate the influence of solar chimneys in the natural ventilation in buildings located in Brazil. Considering that Brazil is a tropical country and has a great potential for the harnessing of solar radiation, it is intended to verify the hypothesis that the use of this device may increase air movement in indoor spaces contributing to promote thermal comfort for users of these environments. The methodology used to verify this hypothesis was based on comparing the performance of two construction systems: a conventional chimney and a solar chimney. The two models have the same height and dimensions for the air inlet and outlet. This comparison was performed by computer simulations using EnergyPlus software, for eight Brazilian cities located in each one of the bioclimatic zones of Brazil, during winter and summer. The investigated device showed satisfactory performance, increasing natural ventilation during the day in all cities simulated, even in winter, when natural ventilation may not be desired in some climates. The data were presented to facilitate the understanding of professionals in the Construction Industry in general, contributing to establish a theoretical framework on the subject, and projective guidelines for more efficient buildings from the standpoint of energy. It is also intended to contribute to the potential of this device is investigated in several Brazilian regions, always trying to adapt the buildings to the climate of where it will be built.
Solar Chimney as alternative to increase the natural ventilation in indoor spaces
Keywords: Construção civil; Conforto ambiental; Economia de energia; Ventilação natural; Chaminé solar; EnergyPlus; Natural ventilation; Solar Chimney; EnergyPlus; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL